2022
DOI: 10.1186/s12864-022-08772-6
|View full text |Cite
|
Sign up to set email alerts
|

DCSE:Double-Channel-Siamese-Ensemble model for protein protein interaction prediction

Abstract: Background Protein-protein interaction (PPI) is very important for many biochemical processes. Therefore, accurate prediction of PPI can help us better understand the role of proteins in biochemical processes. Although there are many methods to predict PPI in biology, they are time-consuming and lack accuracy, so it is necessary to build an efficiently and accurately computational model in the field of PPI prediction. Results We present a novel seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Chen et al [ 53 ] designed the Double-Channel-Siamese-Ensemble (DCSE) model, a sequence-based computational approach, for pairwise PPI prediction, with superior performance. Additionally, Gao et al [ 54 ] developed EResCNN, a predictor for PPIs based on an ensemble residual convolutional neural network, outperforming existing models in PPI prediction on various datasets.…”
Section: Convolutional Neural Network For Protein–protein Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [ 53 ] designed the Double-Channel-Siamese-Ensemble (DCSE) model, a sequence-based computational approach, for pairwise PPI prediction, with superior performance. Additionally, Gao et al [ 54 ] developed EResCNN, a predictor for PPIs based on an ensemble residual convolutional neural network, outperforming existing models in PPI prediction on various datasets.…”
Section: Convolutional Neural Network For Protein–protein Interactionsmentioning
confidence: 99%
“…The trade-off between model complexity and interpretability is another substantial challenge. As seen in studies like Soleymani et al [ 77 ] and Chen et al [ 53 ], deep learning models can be highly complex with numerous layers and nodes, leading to improved predictive performance. However, this complexity can often compromise interpretability, making it challenging to extract biological insights from the models.…”
Section: Challenges and Future Directions In Recent Studiesmentioning
confidence: 99%
“…For instance, LSTM-PHV method [ 8 ] and other related approaches [ 25 ] leveraged the LSTM (Long Short-Term Memory) model to capture long-range dependency features in protein sequences. Methods like ADH-PPI [ 26 ] and DCSE [ 27 ] integrated CNN and RNN to extract both local and long-range features from protein sequences, which were then combined to predict PPI. Attention mechanisms have also been widely utilized to identify key sequence features in protein sequences [ 23 , 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused our attention on sequence-based approaches because of the advantages of rich and easy-to-search protein sequence data sources compared to protein structure data sources [ 2 ]. In addition, numerous tests have shown that amino acid sequence information alone is capable of identifying new protein–protein interactions [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%